Recovery after a shoulder injury - Silva, R. (2001)
Background The shoulder joint is a common site of injury in tennis players. It is therefore important that sports medicine physicians diagnose and treat shoulder injuries correctly, in order to prevent professional and junior athletes from being sidelined for long periods of time. This presentation discusses a number of key issues in the management of shoulder injuries in competitive tennis players.